2012
DOI: 10.3389/fpsyg.2012.00091
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Self-Esteem in Borderline Personality and Depersonalization Disorder

Abstract: Self-perception is disrupted in people with borderline personality disorder (BPD) and depersonalization disorder (DPD), fluctuating with sudden shifts in affect in BPD and experienced as detached in DPD. Measures of implicit self-esteem (ISE), free from conscious control and presentation biases, may highlight how such disruptions of self-concept differentially affect these two populations on an unconscious level. We examined ISE using the Implicit Association Test, along with measures of emotion, behavior, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
5
1
1
Order By: Relevance
“…Contrary to our findings, studies assessing implicit self-esteem with the IAT in BPD report no significant differences between BPD and HC groups (Hedrick & Berlin, 2012;Vater et al, 2013). It would be premature to draw conclusions, as this literature is scarce.…”
Section: Self-positivity In Bpd 15contrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, studies assessing implicit self-esteem with the IAT in BPD report no significant differences between BPD and HC groups (Hedrick & Berlin, 2012;Vater et al, 2013). It would be premature to draw conclusions, as this literature is scarce.…”
Section: Self-positivity In Bpd 15contrasting
confidence: 99%
“…The IAT assesses the strength of associative bonds (i.e., speed of categorization) between self ("I") and positive (e.g., "good") or negative (e.g., "bad") stimuli versus another person (e.g., "other") and said stimuli. The study revealed no BPD-HC differences in the strength of implicit associations between the self and positive information, and between the self and negative information (Hedrick & Berlin, 2012;Vater et al, 2013). Another study (Vater, Schroder-Abe, Schutz, Lammers, & Roepke, 2010) used the Initials Preference Task (IPT; Kitayama & Rarasawa, 1997;Nuttin, 1985).…”
Section: Self-positivity In Bpdmentioning
confidence: 95%
“…Surprisingly, identity disturbances and self-esteem instability have received little empirical attention (Santangelo, Bohus, & Ebner-Priemer, 2014). Even though several studies examined aspects of altered self-esteem in BPD such as trait self-esteem (Roepke et al, 2011), implicit self-esteem (Hedrick & Berlin, 2012), and discrepancies between explicit and implicit self-esteem (Vater, Schröder-Abé, Schütz, Lammers, & Roepke, 2010), heightened instability in the self-esteem of patients with BPD using e-diaries has not been demonstrated empirically. This is surprising, as there is ample empirical evidence that unstable self-esteem is associated with a myriad of BPD-like symptoms in healthy subjects' everyday lives (for a review, see Winter, Bohus, & Lis, 2017; for more details, see Appendix S1 in the online supplementary material): Self-esteem instability (either by itself or in combination with self-esteem level) is associated with diminished self-concept clarity and lower self-acceptance.…”
mentioning
confidence: 99%
“…ESE measures might be influenced by the patients' volatile emotions (Hedrick & Berlin, 2012). Measures of ISE, however, might reveal a non-reflective knowledge about the self (Winter et al, 2017).…”
Section: Identity Self-concept and Self-esteem In Bpdmentioning
confidence: 99%